Answer:
equation 1
y = -2x
equation 2
y = x-3
Solution to both
(1,-2)
Step-by-step explanation:
We need to get the equations of both lines
General form is;
y = mx + c
where m is slope and c is the y-intercept
Table 1
since we have a point 0,0; the y-intercept here is zero
Let us get the slope. We can do this by selecting any two points
m = (y2-y1)/(x2-x1)
m = (2-10)/(-1+5) = -8/4 = -2
So the equation of the first line is;
y = -2x
Table 2
we get the slope
m = (4+2)/(7-1) = 6/6 = 1
The partial equation is;
y = x + c
To get c, we select any two point and substitute
4 = 7 + c
c = 4-7
c = -3
So the equation is;
y = x-3
To get the solution to both systems, we equate the y
-2x = x - 3
-2x-x = -3
-3x = -3
x = -3/-3
x = 1
To get y, we substitute;
recall; y = -2x
y = -2(1)
y = -2
Solution to the system is;
(1,-2)
The solution to the given differential equation is yp=−14xcos(2x)
The characteristic equation for this differential equation is:
P(s)=s2+4
The roots of the characteristic equation are:
s=±2i
Therefore, the homogeneous solution is:
yh=c1sin(2x)+c2cos(2x)
Notice that the forcing function has the same angular frequency as the homogeneous solution. In this case, we have resonance. The particular solution will have the form:
yp=Axsin(2x)+Bxcos(2x)
If you take the second derivative of the equation above for yp , and then substitute that result, y′′p , along with equation for yp above, into the left-hand side of the original differential equation, and then simultaneously solve for the values of A and B that make the left-hand side of the differential equation equal to the forcing function on the right-hand side, sin(2x) , you will find:
A=0
B=−14
Therefore,
yp=−14xcos(2x)
For more information about differential equation, visit
brainly.com/question/18760518
Answer:
v= 1.7in
Step-by-step explanation:
Answer:
$1171.05
Step-by-step explanation:
1500 × (1-(6 / 100))⁴
Answer:
51.7°
Step-by-step explanation:
The mnemonic SOH CAH TOA reminds you that ...
Tan = Opposite/Adjacent
tan(D) = EF/FD = 95/75
D = arctan(95/75)
∠D ≈ 51.7°